Reach In and Feel Something: On the Strategic Reconstruction of Touch in Virtual Space. (July 2014) - Parisi, David
The drive to make human–computer interactions more efficient and effortless has pushed interface designers to think about new methods of information transmission, display and manipulation. The incorporation of haptic feedback cues into the computer interfacing schematic allows the tactile channel to be opened up as a means of complementing and challenging the data provided by the senses of seeing and hearing. In this article, using the Novint Corporation's Falcon three-dimensional touch interface as a case study, the author examines the strategic aims of animating and scaling computer-generated space for the haptic. Spaces of heterogeneous scales, from the microscopic to the macroscopic, can be rendered as analogous force sensations using the Falcon's three-dimensional workspace. The author argues that the project of incorporating complex touch feedback into computing entails not just a transformation of spatiotemporal field accessed by touch, but a wholesale redefinition and rearticulation of touch as a category of human experience.